ARISTOTLE’S “POETICS” AND ITS INTERPRETATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article explores the theoretical issues of literary criticism, including literary-critical information about the concept of poetics. Opinions in this regard are illustrated by the example of Aristotle's Poetics. The article also provides information on concepts such as pathos, catharsis, mimesis.